Multimodal imaging shows acute multilayered retinal hemorrhages in heatstroke–a rare case report - Zhang, Yi; Lei, Chunyan; Huang, Xi; Zhang, Meixia (Frontiers in Medicine, 2024)
Background Heatstroke is a life-threatening disease clinically characterized by central nervous system dysfunction, multiorgan failure, and extreme hyperthermia. There are no reports about eye involvement in heat stroke. Here, we report a rare case of multilayered retinal hemorrhages in a patient with heatstroke. Case presentation A 55-year-old male with a one-month history of blurry vision in both eyes presented at our department after suffering from heatstroke. His visual acuity was 5/20 OD and 10/20 OS. Fundus examination revealed retinal hemorrhages in both eyes. Fundus autofluorescence images and near-infrared reflectance images revealed well-defined retinal lesions. Optical coherence tomography helped to accurately locate the different layers of the lesions, including the nerve fiber layer, sub-inner limiting membrane, outer plexiform layer, ellipsoid zone and Henle fiber layer hemorrhages. We followed up with the patient for 8 months. At the last follow-up, his visual acuity was 20/20 in both eyes, and fundus examination showed that retinal hemorrhages were almost completely absorbed. Conclusion To our knowledge, this is the first report on multilayered retinal hemorrhages secondary to heat stroke. Intraretinal and preretinal hemorrhages can gradually resolve, and the patient’s vision will improve with the absorption of the retinal hemorrhages. Multimodal imaging may help to reveal additional details about retinal lesions and monitor the course of the disease.